Optimization of Medical Device Inventory Planning with the Apriori Method at Malahayati Pharmacy Medan - Rahmadsyah, Andi; Batubara, Rini Oktari (LPPM Universitas Potensi Utama, 2025)
Malahayati Islamic Hospital (RSIM) is a General Hospital engaged in the field of medical or health services for the community, with the aim of assisting the government in serving the community in the field of health and improving the quality of public health, both physical, spiritual and social health. In this hospital there is a pharmacy that helps patients and other medical personnel to obtain medicines and medical devices needed in its management, often the availability of medical devices in the warehouse is very minimal and errors often occur in data collection. In planning the supply of medical devices, the pharmacy finds it difficult to find out information about which types of medical devices are most in demand so that in the future they will increase stock in the warehouse. This can make customers dissatisfied in receiving services, errors in data management that still uses manual methods and is not yet systematic. To overcome this, a system is needed that can be used to find out forecasting using the Apriori Method. In the design and manufacture of this system, the Visual Basic (VB) 2010 application and data storage using the SQL Server 2008 database are used. With this system, it can help the pharmacy to find out information on the supply of medical devices that will come to the Malahayati pharmacy.